Hong Kong Murders - Wilhelm, Katherine (Columbia Journal of Asian Law, 2001)
Crime is a revealing lens through which to see any society. There are few better ways to understand the pressures a society puts on its members, the standards it sets for success and the price it exacts for failure than to comb through its crime annals. That is what Kate Whitehead has done in Hong Kong Murders. Her collection of 14 of Hong Kong’s most flamboyant true-crime stories highlights the pressures of living in one of the most densely populated cities on earth, where those caught up in an endless grind of low-paid work are daily thrown into proximity with gaudy displays of new wealth. It is a world in which neighbors, schooled to respect each other’s privacy, hesitate to call the police even when the smell of death pervades their apartment building, and in which young boys find companionship and upward mobility by joining criminal gangs called triads. Whitehead, a reporter for Hong Kong’s South China MorningPost newspaper, portrays loners and losers as well as self-made crime bosses and opportunistic strivers in a colorful, if ultimately depressing, roster of locally famous criminals and their victims. Lam Kwok-wai, an unemployed school dropout, terrorized the women of Tuen Mun, one of Hong Kong’s soulless high-rise “new towns,” for months in 1992 when he began raping and killing women in the stairwells and elevators of their apartment buildings.